Analysis of Electoral Fraud and its Alternative Efforts: a case study in banguntapan: Analisis Kecurangan Pemilu dan Upaya Alternatifnya: studi kasus di Banguntapan - Mohammad Jailani (Tunas Harapan Ummat Foundation, 2024)
The occurrence of fraud, injustice, and dishonesty in the validation of election data by the Election Team and Committees from villages to the capital city. This happens everywhere, caused by the competition for popularity and tight competition among the different camp teams. Therefore, researchers intend to investigate the occurrence of election fraud in 2019. This research aims to identify the problems of election fraud and valid election data, especially in the Special Region of Yogyakarta in the Wirokerten area, Banguntapan Bantul. The setting of this research is in the Wirokerten area of Banguntapan Bantul Yogyakarta. The subjects of this research consist of village heads, election committee teams, potential voters, former voters in 2019, and local communities. The selection of research subjects is carried out with honesty and data validity. It means researchers have directly asked and met directly with informants or research subjects. Research subjects are selected based on gender perspective and informant character. This research is qualitative, a type of case study research, namely the case of the 2019 election and the upcoming 2024 election. Data is collected through direct interviews and direct observation at the location.